2020
DOI: 10.1523/jneurosci.0407-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

CREB Coactivator CRTC2 Plays a Crucial Role in Endothelial Function

Abstract: The cAMP pathway is known to stabilize endothelial barrier function and maintain vascular physiology. The family of cAMPresponse element binding (CREB)-regulated transcription coactivators (CRTC)1-3 activate transcription by targeting the basic leucine zipper domain of CREB. CRTC2 is a master regulator of glucose metabolism in liver and adipose tissue. However, the role of CRTC2 in endothelium remains unknown. The aim of this study was to evaluate the effect of CRTC2 on endothelial function. We focused the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…MiR-132/212 is a well-studied miRNA cluster in CNS disorders such as neurogenerative diseases [ 26 ] and intracerebral hemorrhage [ 27 ]. CREB-regulated transcription coactivator (CRTC) includes CRTC1, CRTC2, and CRTC3, among which CRTC2 has been demonstrated to dictate the vascular endothelial function [ 28 ], and CRTC1 is a specifically expressed protein in neuron. CRTC1 has been suggested to act as a critical role in several neurodegenerative diseases, such as Alzheimer’s disease [ 29 31 ], and Huntington’s disease [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-132/212 is a well-studied miRNA cluster in CNS disorders such as neurogenerative diseases [ 26 ] and intracerebral hemorrhage [ 27 ]. CREB-regulated transcription coactivator (CRTC) includes CRTC1, CRTC2, and CRTC3, among which CRTC2 has been demonstrated to dictate the vascular endothelial function [ 28 ], and CRTC1 is a specifically expressed protein in neuron. CRTC1 has been suggested to act as a critical role in several neurodegenerative diseases, such as Alzheimer’s disease [ 29 31 ], and Huntington’s disease [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Photochemically induced thrombosis ( PIT) leading to cerebral infarction was developed according to the method we had previously reported 49 . Adult male and female mice aged 8–12 weeks were anesthetized with isoflurane in an induction chamber with 100% oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments have shown that CRTC2 is highly expressed in endothelial cells and is related to the formation of blood vessels. Under the condition of ischemia, CRTC2 can protect the integrity of endothelial cells through P190RhoGAP‐a, and the cAMP pathway can also stabilize the endothelial barrier function, to maintain the physiological function of blood vessels (Kanki et al 2020). The concept that vascular smooth muscle cells (VSMCs) exist in a transitional phase between atherosclerotic smooth muscle and foam cells in humans was first proposed with the help of electron microscopy in 1961(Geer et al 1961).…”
Section: Crtc2 and Metabolism‐related Diseasesmentioning
confidence: 99%
“…With the aggravation of heart failure, the myocardial blood supply gradually decreases. When the myocardium is in a state of ischemia, P190RhoGAP‐a is activated, which affects the angiogenesis, reduces the endothelial barrier function, aggravates heart failure, and further decreases the blood supply, forming a vicious cycle (Kanki et al 2020). Therefore, CRTC2 can affect the structure and active site of CRTC2 in heart failure through SREBP and its effect on endothelial cells.…”
Section: Crtc2 and Metabolism‐related Diseasesmentioning
confidence: 99%